Metal- and solvent-free domino reaction of 2-isocyanophenol esters to benzoxazines: long-range 1,5-acyl migration on 1,4-diazabutatriene - Akbari, Alireza; Khosravi, Hormoz; Bauer, Felix; Rominger, Frank; Breit, Bernhard; Balalaie, Saeed (Chemical communications, 2024)
The first example of intramolecular nucleophilic addition of 1,4-diazabutatriene to ester is disclosed. This approach provides a facile and versatile synthesis for functionalized 2H-1,4-benzoxazines under metal-, reagent-, and solvent-free conditions. Experimental and computational studies revealed the pivotal role of 1,5-acyl migration as the self-catalytic step in the reaction selectivity.